Visualizing institutional logics in sociomaterial practices - Hultin, Lotta; Mähring, Magnus (Information and organization, 2014)
This paper aims to deepen our understanding of the mechanisms underlying the mutual constitution of competing institutional logics and sociomaterial entanglements by combining a sociomaterial lens with the institutional logics perspective. We present findings from an interpretive, longitudinal case study at the emergency general surgery ward of a Nordic university hospital. By focusing our analysis on how sociomaterial affordances emerge through the implementation, use and continued development of digital and physical visualization boards, we show how these artifacts constitute an integral part of the operational staff's sensemaking and enactment of a new institutional logic. We make two contributions. First, we show how the perceived affordances of a technology are created from the experience of using several different technologies and how the rejection of one technology can simultaneously constitute another. Second, we show how visualization artifacts, entangled in sociomaterial practices, can shape individual focus of attention and thus facilitate the integration of a new institutional logic in operational practice. •Visualization artifacts are integral to sensemaking and enacted institutional logics.•These artifacts, IT-based as well as physical, structure work practices.•They shape individual focus of attention and integrate new logics into practices.•Affordances are created from the experience of using several different technologies.•Rejection of a technology constitutes entanglement of other technologies in practice.